Relasi Sunni-Syiah: Refleksi Kerukunan Umat Beragama di Bangsri Kabupaten Jepara - Sulaiman Sulaiman (LP2M UIN Sunan Kalijaga, 2017)
Lately, Sunni-Shia relation gets a negative response in the Indonesian community. This article based on the research results “The Relation of Sunni-Shia in Bangsri, Jepara, Central Java”. This studyused a descriptive qualitative approach, and data collected with observation,depth interview, and document review. The sosial relation between Sunni-Shia is very harmonious, because it’ssupported by religious tolerance highly. It can be seen in the attitude of both sides to understand and aware toward doctrinal differences which believed. In addition, it can be seen too at the culture of ‘gotong royong’ community that is institutionalized in the associations “jamaah Muawanah” and “Jamaah Manakib”. Both these associations becomea medium of muslim in maintaining the harmony and peace of the religious community.